Risk Analysis XII 2020
DOI: 10.2495/risk200141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Use and Communication of Seismic Hazard Maps: A Case Study of Metro Vancouver, British Columbia, Canada

Abstract: The Metro Vancouver region of southwestern British Columbia, Canada, is exposed to significant earthquake risk. Earthquake hazard has yet to be mapped to an effective scale in Metro Vancouver and so it is critical to generate comprehensive seismic hazard maps for the region. The Metro Vancouver Seismic Microzonation Project is tasked with the assessment and mapping of earthquake shaking hazard and liquefaction and landslide susceptibility hazards at a 1:25,000 scale. The detailed hazard information and data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This may have made it easier to identify these cities as having a medium (and sufficiently important) hazard level. Furthermore, these classes were orange in the redesign and blue or green in the baseline; as found in multiple studies (Fyfe and Molnar, 2020;Miran et al, 2017;Thompson et al, 2015), orange may be better associated in Western cultures with damaging hazard than blue/green.…”
Section: Assessing the Redesigned German Seismic Hazard Mapmentioning
confidence: 69%
See 4 more Smart Citations
“…This may have made it easier to identify these cities as having a medium (and sufficiently important) hazard level. Furthermore, these classes were orange in the redesign and blue or green in the baseline; as found in multiple studies (Fyfe and Molnar, 2020;Miran et al, 2017;Thompson et al, 2015), orange may be better associated in Western cultures with damaging hazard than blue/green.…”
Section: Assessing the Redesigned German Seismic Hazard Mapmentioning
confidence: 69%
“…In Padilla et al (2016), participants saw elevation maps using either continuous or discrete classification schemes and were more error-prone with the continuous map compared to the discrete maps, particularly for tasks requiring a steepness judgment. Marti et al (2019) also found that participants had complaints about the continuous color scale the authors used in their seismic hazard maps and suggested that a discrete map would be more effective, as was echoed by Fyfe and Molnar (2020).…”
Section: Criteria For Selecting Color Palettesmentioning
confidence: 97%
See 3 more Smart Citations